Przestrzenie lokalnej demokracji. Szkic z gdańskiej perspektywy - Mendel, Maria (Pedagogika Społeczna Nova, 2021)
This article is an expression of thinking about the spaces of local democracy, which was based on the research project “Gdańsk as a Shared Place” (2014–2015). Due to the fact that the theses and results of this ‘old’ project are updated in the light of the deepening crisis of the social in the pandemic conditions, I present in the article the content selected from the research report, hopefully emphasizing their impor- tance in shaping various, sometimes surprising forms and places of democracy. I am doing this, counting on the fruitful expansion of the field of understanding and practicing bond-forming, communal forms of social life. Thus, I follow the path that Professor Stanisław Kawula (1939–2014) pioneered in social pedagogy, tirelessly describing the social condition and – thus – updating the dimensions of democracy in various perspectives [for example, in relation to the diagnosed risks (2003; 2005 etc.)]. Hence, I dedicate this text to him, and choosing the horizon of local experience, I want to draw attention to the meaning of research descriptions of this local dimension, which is especially important today, in a social crisis condi- tion. I conclude with a reflection on the meanings of non-consensual democracy, inscribed in urbanity as a way of social life, and emphasize the importance of a neighborhood which – literally: having a place – locates democracy in a special way. Such a location allows us to capture its essential meanings and show the democratic productivity of everyday, neighborly production of commonality, that is the common good, constantly crumble and constantly arouse mutual attention and ask for care.